Reducing project bottleneck by transforming organisational culture in pt transtel universal using knowledge management model - Harry Fajar Surya; Achmad Fajar Hendarman (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2023)
The research was conducted to determine whether transforming the company culture would have a positive impact on the organization of PT Transtel Universal. The implementation of the new method by the new management will slightly carry the positive trendline leading the company into efficiency. The implementation of knowledge management would bring efficiency in all aspects especially in operation while handling the project. The operation was previously only based on the basic business now after the new method, the company will grow and keep up with the business ecosystem. Before the transformation, the company only have four divisions, Finance-Human Resource Division, Logistics Division, Sales Division, and Technic Division. That’s one of the concerns that the newly appointed vice president comes in mind to open the new division and tackle all the challenges to finish and bring the best solution to the customers. The method that will be used in the research is a qualitative method by conducting interviews with the managers. The result showed: (1) Transforming the organizational culture is significantly influenced by the leadership system to resolve the bottleneck, (2) The transformation derives from the leadership method influenced by the knowledge simple management method that is used in PT Transtel Universal, (3) Organisational Culture massively influences the process of transferring knowledge management among the employees in PT Transtel Universal.